Extracellular Matrix Stiffness Regulates Osteogenic Differentiation through MAPK Activation - Hwang, Jun-Ha; Byun, Mi Ran; Kim, A. Rum; Kim, Kyung Min; Cho, Hang Jun; Lee, Yo Han; Kim, Juwon; Jeong, Mi Gyeong; Hwang, Eun Sook; Hong, Jeong-Ho (PLOS ONE, 2015)
Mesenchymal stem cell (MSC) differentiation is regulated by the extracellular matrix (ECM) through activation of intracellular signaling mediators. The stiffness of the ECM was shown to be an important regulatory factor for MSC differentiation, and transcriptional coactivator with PDZ-binding motif (TAZ) was identified as an effector protein for MSC differentiation. However, the detailed underlying mechanism regarding the role of ECM stiffness and TAZ in MSC differentiation is not yet fully understood. In this report, we showed that ECM stiffness regulates MSC fate through ERK or JNK activation. Specifically, a stiff hydrogel matrix stimulates osteogenic differentiation concomitant with increased nuclear localization of TAZ, but inhibits adipogenic differentiation. ERK and JNK activity was significantly increased in cells cultured on a stiff hydrogel. TAZ activation was induced by ERK or JNK activation on a stiff hydrogel because exposure to an ERK or JNK inhibitor significantly decreased the nuclear localization of TAZ, indicating that ECM stiffness-induced ERK or JNK activation is important for TAZ-driven osteogenic differentiation. Taken together, these results suggest that ECM stiffness regulates MSC differentiation through ERK or JNK activation.